KAJIAN TERHADAP UU NO. 28 TAHUN 2007 TENTANG KETENTUAN UMUM DAN TATA CARA PERPAJAKAN (Fokus Ekonomi, 2008)
To eliminate obligation of secrecy is one of breakthrough done by Dirjen Pajak to get data is including taxpayer data. Actually confidentiality obligation can be eliminated, but investigation should be done if there is initial evidence that the tax payer does criminal act. This is done so that bank can still be trusted by public to keep their money in or to do other transaction. Key words: Tax, Gap and Obligation